2022
DOI: 10.3390/agronomy12071497
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Estimation of Apple Leaf Photosynthetic Pigment Content Using Fractional Derivatives and Machine Learning

Abstract: As a key functional trait, leaf photosynthetic pigment content (LPPC) plays an important role in the health status monitoring and yield estimation of apples. Hyperspectral features including vegetation indices (VIs) and derivatives are widely used in retrieving vegetation biophysical parameters. The fractional derivative spectral method shows great potential in retrieving LPPC. However, the performance of fractional derivatives and machine learning (ML) for retrieving apple LPPC still needs to be explored. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
2
0
2
Order By: Relevance
“…Полученные результаты показали, что для бесконтактного определения содержания пигментов в листьях яблони можно использовать простые вегетационные индексы, но они должны быть адаптированы для конкретного сорта. Качество результатов при этом вполне сопоставимо с таковым, полученным на основе методов машинного обучения (19) или методов, основанных на использовании нейронных сетей (20). При этом в отличие от сложных методов, предлагаемые нами подходы более просты в использовании.…”
Section: спектральные вегетационные индексы для бесконтактного опреде...unclassified
See 1 more Smart Citation
“…Полученные результаты показали, что для бесконтактного определения содержания пигментов в листьях яблони можно использовать простые вегетационные индексы, но они должны быть адаптированы для конкретного сорта. Качество результатов при этом вполне сопоставимо с таковым, полученным на основе методов машинного обучения (19) или методов, основанных на использовании нейронных сетей (20). При этом в отличие от сложных методов, предлагаемые нами подходы более просты в использовании.…”
Section: спектральные вегетационные индексы для бесконтактного опреде...unclassified
“…Причем во многих публикациях акцент сделан на разработке новых методов извлечения информации о содержании пигментов в растениях. Так, для листьев яблони в Китае (19,20) (22), каротиноиды -методом фон Ветштейна (23).…”
unclassified
“…Cheng et al predicted the photosynthetic pigments in apple leaves using fractional derivatives to augment the data and range of machine learning algorithms, i.e., support vector machines, k-nearest neighbor, random forest, and neural networks [38]. In [39], it is shown that a similar approach using a different algorithm, XGBoost, can be used to estimate the moisture content of agricultural soil.…”
Section: Spectroscopymentioning
confidence: 99%
“…Cheng et al predict the photosynthetic pigments in apple leaves using fractional derivatives to augment the data and range of machine learning algorithms, i.e., support vector machines, k nearest neighbor, random forest, and neural networks, [37]. In [38], it is shown that a similar approach though using a different algorithm, XGBoost, can be used to estimate agricultural soil moisture content.…”
Section: Spectroscopymentioning
confidence: 99%